2020
DOI: 10.3390/ijms21176058
|View full text |Cite
|
Sign up to set email alerts
|

Precocious Downregulation of Krüppel-Homolog 1 in the Migratory Locust, Locusta migratoria, Gives Rise to An Adultoid Phenotype with Accelerated Ovarian Development but Disturbed Mating and Oviposition

Abstract: Krüppel-homolog 1 (Kr-h1) is a zinc finger transcription factor maintaining the status quo in immature insect stages and promoting reproduction in adult insects through the transduction of the Juvenile Hormone (JH) signal. Knockdown studies have shown that precocious silencing of Kr-h1 in the immature stages results in the premature development of adult features. However, the molecular characteristics and reproductive potential of these premature adult insect stages are still poorly understood. Here we report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…The resulting JH-Met-Tai complex induces the expression of JH response genes, including the gene coding for Krüppel-homolog 1 (Kr-h1), a Zn-finger containing transcription factor [5,6]. RNA interference (RNAi) studies have demonstrated the importance of the JH receptor Met, as well as the downstream-acting transcription factor Kr-h1, in mediating the anti-metamorphic effects of JH in the red flour beetle Tribolium castaneum, the German cockroach Blattella germanica, the kissing bug Rhodnius prolixus, the two-spotted cricket Gryllus bimaculatus, the brown planthopper Nilaparvata lugens, the common bed bug Cimex lectularius, the migratory locust Locusta migratoria and the fire bug Pyrrhocoris apterus [7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The resulting JH-Met-Tai complex induces the expression of JH response genes, including the gene coding for Krüppel-homolog 1 (Kr-h1), a Zn-finger containing transcription factor [5,6]. RNA interference (RNAi) studies have demonstrated the importance of the JH receptor Met, as well as the downstream-acting transcription factor Kr-h1, in mediating the anti-metamorphic effects of JH in the red flour beetle Tribolium castaneum, the German cockroach Blattella germanica, the kissing bug Rhodnius prolixus, the two-spotted cricket Gryllus bimaculatus, the brown planthopper Nilaparvata lugens, the common bed bug Cimex lectularius, the migratory locust Locusta migratoria and the fire bug Pyrrhocoris apterus [7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In the soft tick, Ornithodoros moubata, Spook expression was determined in the ovary from both final instar nymphs and adult females, and shade expression was frequently surged after engorgement and copulation in adult females, suggesting Spook and shade are involved in ovary development [30]. Similar expression was also detected in the Varroa mite, Varroa destructor [31], and in the migratory locust, Locusta migratoria [32]. In the rice planthopper, Nilaparvata lugens, silencing the expression of the Spookier led to less oviposition [8].…”
Section: Introductionmentioning
confidence: 74%
“…Because the synthesis of insect Vg is generally regulated by juvenile hormones (JH; Song et al, 2014 ; Lyu et al, 2019 ; Gijbels et al, 2020 ), and JH plays major roles in development, ovary maturation, and reproduction in insects ( Riddiford et al, 2003 ), genes related to JH synthesis and degradation were examined, including JHAMT (juvenile hormone acid methyltransferase), FAMET (farnesoic acid O-methyltransferase), and JHE (juvenile hormone esterase). After ds NlSLC26A10 treatment, the expression level of JHAMT decreased at 2 d.p.i., and significantly decreased at 3 and 5 d.p.i., compared with the ds GFP treatment ( Figure 9C ).…”
Section: Resultsmentioning
confidence: 99%